The role of the interface in germanium quantum dots: when not only size matters for quantum confinement effects12. Issue 26 (16th June 2015) - Cosentino, S.; Mio, A. M.; Barbagiovanni, E. G.; Raciti, R.; Bahariqushchi, R.; Miritello, M.; Nicotra, G.; Aydinli, A.; Spinella, C.; Terrasi, A.; Mirabella, S.
Abstract : This work elucidates the interplay between quantum confinement and interface effects in the optical properties of Ge quantum dots, demonstrating that not only size matters at the nanoscale. Abstract : Quantum confinement (QC) typically assumes a sharp interface between a nanostructure and its environment, leading to an abrupt change in the potential for confined electrons and holes. When the interface is not ideally sharp and clean, significant deviations from the QC rule appear and other parameters beyond the nanostructure size play a considerable role. In this work we elucidate the role of the interface on QC in Ge quantum dots (QDs) synthesized by rf-magnetron sputtering or plasma enhanced chemical vapor deposition (PECVD). Through a detailed electron energy loss spectroscopy (EELS) analysis we investigated the structural and chemical properties of QD interfaces. PECVD QDs exhibit a sharper interface compared to sputter ones, which also evidences a larger contribution of mixed Ge-oxide states. Such a difference strongly modifies the QC strength, as experimentally verified by light absorption spectroscopy. A large size-tuning of the optical bandgap and an increase in the oscillator strength occur when the interface is sharp. A spatially dependent effective mass (SPDEM) model is employed to account for the interface difference between Ge QDs, pointing out a larger reduction in the exciton effective mass in the sharper interface case. These results add new insights into the role of interfaces on confined systems, and open the route for reliable exploitation of QC effects.